2022
DOI: 10.1177/17423953221137891
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and risk factors of subsequent lower extremity amputation in patients diagnosed with diabetes in Saskatchewan, Canada

Abstract: Objective Subsequent limb amputation (SLA) may be necessary due to disease progression, infection, or to aid prosthesis fit. SLA in Saskatchewan has increased 3.2% from 2006 to 2019 with minor SLA increasing 9.6% during that period. Diabetes affects a large proportion of patients who require SLA; however, the impact of additional comorbidities is not clear. Methods First-episode subsequent lower extremity limb amputation (SLEA) cases with the presence/absence of diabetes, other comorbidities, and demographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Recent research in the United States has shown that persons identifying as Black and living in rural settings are particularly at risk of a first dysvascular LEA [ 19 , 20 ] compared to those who were non-Black living in urban settings [ 20 ]. In Canada, recent research has shown Indigenous persons are at increased risk for subsequent LEA [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in the United States has shown that persons identifying as Black and living in rural settings are particularly at risk of a first dysvascular LEA [ 19 , 20 ] compared to those who were non-Black living in urban settings [ 20 ]. In Canada, recent research has shown Indigenous persons are at increased risk for subsequent LEA [ 21 ].…”
Section: Introductionmentioning
confidence: 99%